THE CAUCHI PROBLEM FOR THE GENERAL SYSTEM OF CAUCHI-RIEMAN EQUATIONS WITH QUATTERNION PARAMETERS.v - Сатторов Э.Н.; Рустамов С.У. (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this paper, we study the problem of continuing the solution of the generalized Cauchy-Riemann system with a quaternion parameter according to given values on part of the boundary of a given region in three-dimensional space.